Comparison of Multicarrier PWM Techniques for Cascaded H-Bridge Multilevel Inverter - Hashim Hasabelrasul; Xiangwu Yan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
One of the preferred choices of electronic power conversion for high power applications are multilevel inverters topologies finding increased attention in industry. Cascaded H-Bridge multilevel inverter is one of these topologies reaching the higher output voltage, power level and higher reliability due to its modular topology. Level Shifted Carrier Pulse Width Modulation (LSCPWM) and Phase Shifted Carrier Pulse Width Modulation are used generally for switching cascaded H-bridge (CHB) multilevel inverters. This paper compares LSCPWM and PSCPWM in terms of total harmonics distortion (THD) and output voltage among inverter cells. Simulation for 21-level CHB inverter is carried out in MATLAB/SIMULINK and simulation results are presented.